Implementação de um sistema de codificação RELP para fins didáticos - Neto, Carlos (1996)
In this work we implemented a RELP speech coder. This type of coder is well known and presents medium complexity. It is useful to study because it includes different signal processing techniques that are used in more modern and efficient speech coders. Special attention was given to the user’s interface enabling a simple way to change the coding parameters and an easy display of the signals in different stages of the coding process. The system was implemented using Matlab running on MSWindows.